John B. Carroll, The study of language. A survey of linguistics and related disciplines in America. Harvard University Press, Cambridge, Mass., 1953; xiv + 289 pp. - Beym, Richard (Nueva Revista de Filología Hispánica (NRFH), 1954)
Se reseñó el libro: The study of language. A survey of linguistics and related disciplines in America.